DAMPAK DIMENSI INDIVIDUAL FINANCIAL LITERACY TERHADAP FINANCIAL INCLUSION PADA MASYARAKAT PEDESAAN - Ricka Ade Putri; Chairil Afandy (Management Insight: Jurnal Ilmiah Manajemen, 2020)
This study aims to analyze the effect of individual dimensions of financial literacy on financial inclusion. This research design is a survey with an online questionnaire. The object of this research is the people in rural Bengkulu. The respondent in this study was 503 respondents. This study used convenience sampling with screening. This study reveals that knowledge, attitudes, and behaviors influence financial inclusion in rural Bengkulu. While skills do not affect financial inclusion in rural Bengkulu. This research also found that attitude is the variable that has the greatest influence on financial inclusion.